Pengaruh Partisipasi Penyusunan Anggaran, Komitmen Organisasi, dan LOC Pada Kinerja Manajerial Di PDAM Tabanan - Pariono, Ade; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi; Vol 23 No 3 (2018), 2018)
Participation in the preparation of the budget is very important role in the organization, the role is related to the duties and responsibilities as one of the government apparatus engaged in the field of services, the Perusahaan Daerah Air Minum requires employees who can work well for the resulting good managerial performance as well as examine the factors affect the performance of manjerial the participation of budget preparation, organizational commitment, and LOC. The purpose of this study was to determine the effect of budgetary participation, organizational commitment, and LOC on managerial performance. This research uses 193 sample of employees from total population of 313 with purposive sampling method. Data collection method used in this research is questionnaire. Data analysis techniques used to test the hypothesis in this study is multiple linear regression analysis with the help of SPSS program. The result of analysis shows that budget participation has positive effect on managerial performance, organizational commitment has positive effect on managerial performance, LOC has positive effect on managerial performance. Keywords : managerial performance, budgetary participation, organizational commitment and locus of control